A Virtual Environment for Studying Flexible Robot Manipulators - Azad, Abul K. M.; Tokhi, Osman; Shaheed, Hasan (International Journal of Online and Biomedical Engineering (iJOE), 2009)
The paper presents a virtual environment for simulation and modeling a single-link flexible robotic manipulator. Simulation algorithm is based on the finite difference method where the systems governing dynamic equation is discretized and implemented. Intelligent modeling techniques are developed using neural network and genetic algorithm based techniques. All these have been developed and realized within a virtual environment using the Matlab, Simulink, and associated toolboxes. An interactive user friendly graphical user interface has also been presented. This environment has proven to be a valuable educational tool for understanding the behavior of flexible manipulator systems and can also be used as a computer aided teaching facility and a testbed for controller designs.